CRYSTAL CHEMICAL CONTROL OF CLINOPYROXENE-MELT PARTITIONING IN THE DI-AB-AN SYSTEM: IMPLICATIONS FOR ELEMENTAL FRACTIONATIONS IN THE DEPLETED MANTLE - Lundstrom C.C.; Williams Q.; Gill J.; Shaw H.F.; Ryerson F.J. (My University, 1998)
The partitioning of fifteen trace elements (Rb, Sr, Zr, Nb, Ba, La, Ce, Nd, Sm, Gd, Yb, Hf, Ta, Pb, and Th) between clinopyroxene and synthetic melt has been studied in two compositions along an isotherm in the diopside-albite-anorthite ternary at 1 bar pressure. The two compositions correspond to ~Di65An35 and ~Di55Ab45 and produce clinopyroxenes distinct in chemistry while melt compositions range from 49 wt% SiO2 to 61 wt% SiO2. The partition coefficients of high field strength elements (HFSE) increase by factors of 2–8 in Di-An experiments relative to Di-Ab experiments while other elements show very little change (±20%) between compositions. The change in HFSE partitioning correlates with increases in tetrahedral Al203 (IVAl) content of clinopyroxenes in the anorthite-bearing experiments. Changes in DTa/DNb also correlate with IVAl based on a survey of previously published determinations.